2013
DOI: 10.1117/1.jrs.7.073487
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nocturnal low-level jet–generated gravity waves over Oklahoma City during morning boundary layer transition period using Doppler wind lidar data

Abstract: Abstract. Low-level jet (LLJ)-generated gravity waves were observed over Oklahoma City by a scanning Doppler wind lidar during the transition periods of atmospheric boundary layer (ABL) from stable to convective conditions in the mornings after sunrise. The temperature profiles had a multilayer structure with a shallow neutral layer immediately above the ground and a stable cap layer above the neutral layer. The wind profiles exhibited a typical shape of a LLJ with nearly linear growth of wind speed with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…under conditions in which gravity waves are common features (e.g. Fritts et al, 2003;Newsom and Banta, 2003;Wang et al, 2013). Besides vertical wind shear, some of the gravity waves seem to be linked to orographic features, although obstacle heights upstream of SAVE are on the order of 50 m only.…”
Section: Discussionmentioning
confidence: 99%
“…under conditions in which gravity waves are common features (e.g. Fritts et al, 2003;Newsom and Banta, 2003;Wang et al, 2013). Besides vertical wind shear, some of the gravity waves seem to be linked to orographic features, although obstacle heights upstream of SAVE are on the order of 50 m only.…”
Section: Discussionmentioning
confidence: 99%
“…Single DWLs have been extensively used in ABL studies for both flat and gently variable terrain, [13][14][15][16][17][18][19] over urban areas, [20][21][22][23] and for studies on wind turbine wakes at heights of hundreds of meters. 24 While the assumptions used for single DWL retrievals are appropriate for many situations, they are not suitable for highly complex and spatially variable turbulent flows in mountainous terrain.…”
Section: Introductionmentioning
confidence: 99%
“…For studying AGW, coherent Doppler wind lidars (CDWLs) and sodars are used as well. Newsom and Banta (2003) and Wang et al (2013) applied 2 µm CDWL to investigate of low-level jet and gravity waves in the stable ABL over flat and urban terrains, respectively. Lyulyukin et al (2015) observed AGW in the lower atmospheric layer (300-400 m) based on sodar data.…”
Section: Introductionmentioning
confidence: 99%